HUBUNGAN TINGKAT PENGETAHUAN REMAJA TENTANG OBESITAS DENGAN PENERIMAAN HARGA DIRI REMAJA DI SMP PANGUDI LUHUR 1 TIMOHO YOGYAKARTA - Patria Asda; Sri Kandi sara (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2017)
Background: Obesity teens have become major health problem. Many teens who prioritize  physical appearance (physical appereance) in relationships with peers. They still includes physical things visible from the outside. Therefore, teenagers trying to appear as an individual who attract the attention of others, both peers of the same sex or of the opposite sex. In order to appear as attractive as possible, then a teenager seeking that his body lean and avoid obesity.Objective: To determine the relationship of knowledge about adolescent obesity and adolescent self-esteem reception in SMP Pangudi Luhur 1 Timoho.Methods: This study was an observational study with cross sectional analytic. The subjects were obese adolescents in junior Pangudi Luhur 1 Timoho Yogyakarta. Total population (juvenile obesity) in SMP Pangudi Luhur 1 Timoho Yogyakarta as many as 37 people. Mechanical samplers using total sampling method.Results: The results of this study showed that the majority of teenagers in junior Pangudi Luhur 1 Timoho knowledgeable unfavorable as much (70.3%), and well as many (29.7%), for proceeds of low self-esteem as much (81.1%), and higher by (18.9%). Test chi square correlation between the level of knowledge of adolescents about the relationship of obesity with the acceptance of adolescent self-esteem known sig 0.001, which means there is a positive relationship with the Contingency Cooeficient of (0.509). Conclusion: There was a significant correlation between the level of knowledge about adolescent obesity and adolescent self-esteem reception.